Security Management at the Bromonilan Cup IV Volleyball Tournament in Sleman, Special Region of Yogyakarta - Wantono, Wantono; Yuniati, Nining; Suyanti, Dwi Erma (CV. Publikasi Indonesia, 2026)
Volleyball tournaments in Indonesia often face security challenges due to high spectator enthusiasm and fanatical supporter behavior, with recurring incidents of chaos underscoring the need for effective security management. The community-organized Bromonilan Cup IV tournament in Sleman, Yogyakarta, serves as a relevant case study for examining community-based event security practices. This research aims to identify the factors that affect security and safety at events organized by residents of Bromonilan, Purwomartani, Kalasan, Sleman, Yogyakarta. The fourth Bromonilan Cup volleyball tournament featured matches between local clubs (non-official clubs), but it still presented many highly skilled players, including several national-level athletes. This study uses a descriptive qualitative method, namely interviews with competent figures involved in the volleyball matches at Bromonilan Cup IV in 2025. The results of the study show that the factors determining the safety of a volleyball event include the readiness of the organizing committee—especially the security and parking divisions—the compliance of the match operations division in implementing rules that have been mutually agreed upon, the punctuality and discipline of players entering the court, and the presence of competing teams and star players. In addition, the thoroughness of the match referee in making decisions is also an important factor. The conclusion indicates that maintaining order and security depends on good coordination among the match committee, the accuracy and compliance of the competing teams in fulfilling the established rules, and the presence of the wasit (referee) team from PBVSI who serves as the official leader of the match.